Intelligent souls? : feminist orientalism in eighteenth-century English literature - Cahill, Samara Anne (Transits (Bucknell University), 2019)
"Do women have souls? Christianity has traditionally held the soul to be the seat of reason, intelligence, humanity, immortality, and moral agency. But the Book of Genesis never says that God breathed a soul into Eve. Women's souls thus became significant in Reformation satires as Protestants and Catholics debated whether scripture alone or institutional authority ought to determine interpretation. In England, these satires eventually intersected with what scholars have called the "Trinitarian Controversy," a dispute about the nature of Christ that paralleled the interpretive difficulty regarding the nature of women's souls. In order to marginalize heterodox thinkers who claimed that Christ was not of the same substance as God the Father, orthodox Anglicans collapsed the distinction between schism and heresy by comparing heterodox Christians to a sexualized stereotype of Muslim despots. Part of this stereotype was the (erroneous) claim that Muslim doctrine asserted that women did not have souls and could only experience physical, not intellectual, pleasure. Thus, the problem of competing Christian biblical interpretations could be foisted onto a stereotype of Muslim men as brutal, self-serving misogynists. Englishwomen soon took up the trope to argue that a truly enlightened, and necessarily Christian, Englishman would support improvements in women's education--and feminist orientalism was born"--